Primary tuberculosis of zygomatic bone: A rare case report - Hari Ram; Satish Kumar; Virendra Atam; Madhu Kumar (Elsevier, 2020)
Tubercular osteomyelitis of zygomatic bone is extremely rare. Here we have reported a rarest case of primary tuberculosis (TB) of zygomatic bone in a 20 year male who presented with discharging sinus over right zygomatic region. Anti-tubercular chemotherapy given and patient improved well. Keywords: Zygomatic bone, Tuberculosis, Discharging sinus, Anti-tubercular chemotherapy